2016
DOI: 10.21859/jrehab-1702118
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Parent-Child Stress with Cochlear Implanted Children’s Developmental Skills

Abstract: Objective One of the treatments that have been proposed recently for deaf children is cochlear implant. It is a new technology and an accepted treatment for children with hearing impairment. In recent years, researchers have paid special attention to the family and its relationship with the developmental skills of children with hearing loss. Clinical experience has also shown that emotional performance and psychological problems of the caregiver can have unfavorable effects on cochlear implanted children's dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Finally, the present study showed a positive relationship between parental stress and parental attitude towards the outcomes of CI for aspects of communication abilities and social skills. This finding was not expected as the majority of the investigations have reported a negative relationship between parental stress and the CI outcomes (9,11,(16)(17)(18)(19)26) . Further, Davies (18) reported no correlation between parental stress and parental attitude towards communication skills of children with hearing loss.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Finally, the present study showed a positive relationship between parental stress and parental attitude towards the outcomes of CI for aspects of communication abilities and social skills. This finding was not expected as the majority of the investigations have reported a negative relationship between parental stress and the CI outcomes (9,11,(16)(17)(18)(19)26) . Further, Davies (18) reported no correlation between parental stress and parental attitude towards communication skills of children with hearing loss.…”
Section: Discussionmentioning
confidence: 83%
“…Several studies have investigated the relationship between parental stress and outcomes of children with CI (9,11,(16)(17)(18)(19) . In general, the findings of these investigations have showed a negative correlation between parental stress and outcomes of CI.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations